The role of polymeric additives in water jet cutting. (22nd July 2009) - Annoni, Massimiliano; Monno, Michele; Bertola, Volfango; Goletti, Massimo
The use of additives in water jet (WJ) applications is known since 1970 when Franz (1970) outlined the effect of improved coherence due to additives as a method to increase depth penetration of a WJ. A number of publications exist in literature although a comprehensive study of the different additives effects is not available so far. Early studies (Franz, 1972; Kudin et al., 1973; Zakin and Summers, 1976) point out how the WJ cutting performance is enhanced by certain additives, however, the application of drag-reducing additives to abrasive water jet (AWJ) technology is not well-developed and understood, especially in case of injected jets (Hollinger et al., 1989; Hashish, 1997; Howells, 1999; Louis et al., 2003). The aim of the present study is to develop an injection system suitable to give a quantitative assessment of the effect of various types of additives on the WJ cutting capability. In particular, such system has been applied to investigate the main effects of a polymeric additive in case of WJ machining under a technological point of view (jet behaviour and cutting performance).